Rapid detection of cefotaxime-resistant Escherichia coli by LC-MS - Burrer, Achim; Findeisen, Peter; Grundt, Alexander; Miethke, Thomas; Neumaier, Michael (International journal of medical microbiology, 2015)
Antibiotic resistance is an unsolved healthcare problem with increasing impact on patient management in the last years. In particular, multidrug resistance among Gram-negative bacterial strains has become the most pressing challenge. In order to deliver the most efficacious antimicrobial therapy with minimum delay, rapid diagnostic tests are required in order to detect multidrug resistant pathogens early during infection. In line with these efforts, we have developed a mass spectrometry-based assay for the rapid determination of ampicillin and cefotaxime resistance. The assay quantifies beta-lactamase activities towards ampicillin and cefotaxime within a turnaround time of 150min, which is substantially faster than classical susceptibility testing.